Pengaruh Pengetahuan Kewirausahaan, Kemampuan Manajemen, Digital Marketing, dan Motivasi Kewirausahaan terhadap Keberhasilan Usaha pada Coffee Shop di Kecamatan Gambiran dan Genteng Banyuwangi - Maeyana Kurnia Anggraini; Wahyu Eko Setianingsih; Ira Puspitadewi S (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The growth of the micro, small, and medium enterprises (MSMEs) sector, particularly in the coffee-based culinary field, has shown significant dynamics in various regions, including Gambiran and Genteng Districts of Banyuwangi. Coffee shops have evolved not only as venues for beverage consumption but also as social spaces and integral parts of modern lifestyles. However, the success of coffee shop businesses is influenced by various complex internal factors, including entrepreneurial knowledge, managerial capability, digital marketing, and entrepreneurial motivation. This study aims to examine the influence of these four variables on the success of coffee shop businesses. The research employed a quantitative associative method with data collected through questionnaires distributed to 70 coffee shop entrepreneurs and analyzed using multiple linear regression via SPSS software. The results indicate that all independent variables significantly influence business success, with digital marketing being the most dominant factor, followed by entrepreneurial motivation and management capability. Meanwhile, entrepreneurial knowledge shows a negative influence, suggesting that the accumulation of knowledge without practical implementation may hinder business success. These findings underscore the importance of integrating knowledge capacity with adaptive business practices to achieve sustainable MSME success.